Pengaruh Profitabilitas, Leverage, Ukuran Perusahaan, Dan Capital Intensity Ratio Terhadap Effective Tax Rate (Studi Empiris Pada Perusahaan Sektor Industrials Yang Terdaftar Di Bursa Efek Indonesia Periode 2019 - 2021) - Fisdiyah, Imawati; Suryono, Abi; Marsuking, Marsuking; Setiorini, Kusumaningdiah Retno (Fakultas Ekonomi dan Bisnis Universitas Alma Ata, 2023)
This study aims to empirically examine the effect of profitability, leverage, company size, and capital intensity ratio on the effective tax rate (ETR). This type of research is quantitative research with secondary data from annual reports on the Indonesia Stock Exchange (IDX). The population is 58 industrial companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The sampling technique is non-probability sampling using a purposive sampling method. From the selection results obtained a sample of 10 companies. Data processing uses the IBM SPSS Statistics version 25 application with data analysis in the form of statistical descriptive analysis, classical assumption test, multiple linear regression, hypothesis testing, and determination test. The results showed that profitability has no effect on the effective tax rate, leverage has no effect on the effective tax rate, company size has an effect on the effective tax rate, and capital intensity ratio has no effect on the effective tax rate. Meanwhile, profitability, leverage, company size, and capital intensity ratio together affect the effective tax rate.